Nutritional Status of Children Less Than Five Year Old Suffering Anemia and Night Blindness in Khartoum State, Sudan - Alredaisy, Samir Mohamed Ali Hassan; Saeed, Haram Omer El Hag (Richtmann Publishing, 2012)
This work investigates nutritional status of children less than five year old suffering anemia and nightblindness in Khartoum State with particular emphasis to three central children hospitals in Khartoum,Khartoum north and Omdurman. The sample size was 138 children determined by 10% rate of prevalenceof nutritional deficiency diseases among children living in Khartoum State, and distributed proportionallyaccording to the number of children suffering these two diseases in each hospital. In addition, hemoglobinand anthropometric measurements were done. Results depict that, physical symptoms of anemia are lossof appetite (87.7%), paleness (93.5%), exhaust, and eating clay (29%), while for night blindness they werexerophthalmia (20%); Pinot spots (52%); karatomalacia (12%), and Cornea ulceration (4%). Acutemalnutrition constituted 63% of cases of children suffering anemia and night blindness. Children sufferinganemia and night blindness distributed among different age groups have very low percent of hemoglobinconcentration below 60% standard, confirming for prevalence of Iron deficiency anemia. Malnutrition washighest among children aged 1-3 year old, and females are less malnourished compared to males. Therewas low energy (calories), Iron and Vitamin A levels of intake among these children. Somerecommendations were suggested to reduce anemia and night blindness among children in KhartoumState.